A study on the job satisfaction of secondary school teachers: the case of kandy district in sri lanka - Panditharatne, P.; Wijesundara, S. (University of Jaffna, 2012)
The main purpose of this paper is to describe the level of job satisfaction and to identify the factors that affect the job satisfaction of secondary school teachers in Kandy district. The theoretical frame work used in this study was the “Three Domain Model” which was created by Dinham and Scott, (2000) by revising the Herzberg’s two-factor theory. The study used a ‘mixed’ method design that included a questionnaire survey and a multiple case study. A questionnaire created for the “Teacher 2000 project” by Dinham and Scott, (1998) was adapted in this study to determine the level of job satisfaction and to identify the factors affecting it the sample for the study consisted of 507 secondary school teachers in Kandy district. Present paper discussed only the results of the quantitative phase. It was revealed that the overall job satisfaction of secondary school teachers were low (34.2%). Moreover, the respondent’s initial satisfaction with teaching had changed towards dissatisfaction over time. The application of factor analysis resulted in the extraction of eight factors which fell into all three domains (Dinham and Scott, 2000). The corebusiness of teaching factors included: student achievement, professional self growth, collegial support. The school level factors included: school leadership, climate, decision making and the system level/societal factors included, merit promotion, school reputation, status and image of teachers, workload and the impact of educational reforms. Respondents were most satisfied with corebusiness of teaching factors except with the professional self development factor. They were least satisfied as a whole with System level/Societal factors, School level factor and the opportunities for the professional self development. School level factors showed the most variation, reflecting the influence of the leadership style of the principal. The findings suggest that the actions to improve teacher satisfaction are most likely to be effective at the school level. The confirmatory factor analysis showed that the instrument could explain 61% of the total variance. Therefore, we have decided to conduct case studies (second phase) on selected teachers, to identify further factors which have not included in the Three Domain Model, that affect teacher job satisfaction.
Keywords: Job satisfaction; Secondary School Teachers; Three Domain Model